Towards an Outpatient Model of Care for Motor Functional Neurological Disorders: A Neuropsychiatric Perspective - Saxena A (Dove Medical Press, 2020)
Aneeta Saxena,1,2 Ellen Godena,1 Julie Maggio,1,3 David L Perez1,4 1Functional Neurological Disorder Clinical and Research Program, Cognitive Behavioral Neurology Unit, Department of Neurology, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USA; 2Epilepsy Division, Department of Neurology, Boston Medical Center, Boston University School of Medicine, Boston, MA, USA; 3Department of Physical Therapy, Massachusetts General Hospital, Boston, MA, USA; 4Division of Neuropsychiatry, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USACorrespondence: Aneeta SaxenaMassachusetts General Hospital, Department of Neurology, 55 Fruit Street, Boston, MA 02114, USAEmail asaxena7@mgh.harvard.eduAbstract: Functional neurological disorder (FND), a condition at the intersection of neurology and psychiatry, is a common and disabling outpatient referral to neurology and neuropsychiatry clinics. In this perspective article, we focus on the motor spectrum of FND (mFND), including individuals with functional movement disorders (FND-movt), functional limb weakness/paresis (FND-par) and functional [psychogenic non-epileptic/dissociative] seizures (FND-seiz). Over the past several decades, there have been dedicated efforts within the neurologic and psychiatric communities to create “rule-in” diagnostic criteria, as well as thoughtful approaches to the clinical interview, delivery of the diagnosis and the development of a patient-centered treatment plan. These advances allow the promotion of good clinical practices in the outpatient assessment and management of mFND. Informed by the literature and our prior clinical experiences, we provide suggestions on how to evaluate individuals with suspected functional motor symptoms - including conducting sensitive psychiatric and psychosocial screenings. Additional sections discuss common “rule-in” neurological examination and semiologic signs of motor FND, as well as approaches to deliver the diagnosis and formulate a treatment plan based on individual patient needs. To aid the development of shared (partially overlapping) expertise that catalyzes an interdisciplinary approach to mFND, the use of physiotherapy for therapeutic motor retraining and cognitive behavioral therapy to examine relationships between symptoms, thoughts, behaviors and emotions are also discussed. Additional clinical research is needed to further refine and operationalize the assessment and management of mFND, across clinics, healthcare settings and countries.Keywords: functional movement disorder, dissociative seizures, conversion disorder, psychogenic, treatment, neuropsychiatry